The strategy of Islamic religious education teachers in increasing the values of spiritual intelligence (sq) at the Generation of Mulia Kulon Progo Elementary School, Yogyakarta: Indonesia - Sutarman; Indah Mayangsari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research is motivated by the increasingly widespread juvenile delinquency in Indonesia. Teenagers are supposed to be agents of change but have poor moral values. The aims of this study were (1) to be able to find out the strategies of PAI teachers in increasing the spiritual intelligence and religious knowledge of students at SDIT Generasi Mulia Nanggulan. (2) To find out the supporting and inhibiting factors of Islamic Religious Education teachers in increasing the spiritual intelligence and religious knowledge of students at SDIT Generasi Mulia Nanggulan. (3) To find out the benefits of spiritual intelligence and religious education on student morals. In this study, researchers used a type of qualitative research with a qualitative descriptive approach. Data collection used interview, observation and documentation techniques with primary data of 10 students, 2nd teacher of Islamic Religious Education, and 1st grade teacher. While secondary data obtained through books, journals and internet media that are relevant to this research. The results of this study found that there were three important findings, namely: (1) the teacher's strategy for Islamic religious education in improving students' spiritual intelligence and religious knowledge, namely getting students to practice their prayers properly, Islamic personal development, getting used to reading the Koran and memorizing the Koran 'an, being a good teacher figure, getting students used to being honest, increasing spiritual intelligence through stories, memorizing daily prayers and hadiths, memorizing short letters; (2) the supporting factors are students who easily adjust to places, there is a contribution between parents and teachers. The benefits of spiritual intelligence on student morals are more disciplined, have courtesy and courtesy to teachers and more mature people, carry out worship activities well without having to be reprimanded; (3) Obstacles experienced by teachers in increasing students' spiritual intelligence and religious knowledge, namely from different family environments, environmental associations, social media, lack of parental attention due to busyness and lack of parental understanding of spirituality.